Comparative Analysis of Trans Batam and Trans Jakarta Buses in Improving the Quality of Public Services in Indonesia - Fiza Susanti; Timbul Dompak (Green Social: International Journal of Law and Civil Affairs, 2026)
This study aims to analyze and compare the effectiveness of the Trans Batam and Trans Jakarta bus systems in improving the quality of public services in Indonesia. The issues examined include the factors that influence the success of both mass transportation systems, as well as the challenges they face in their implementation. The research methodology uses a qualitative approach with a literature study as the method of data collection. Data is comprehensively gathered from various sources, including verified scientific journals, official reports from the regional governments of DKI Jakarta and Batam City, as well as credible news articles from national and local media. The data analysis focuses on comparing key aspects such as system planning, integration with other modes of transportation, fleet quality and maintenance, payment systems, and user satisfaction levels. The results of the study show significant differences in terms of implementation, obstacles, and impacts on the quality of public services between Trans Batam and Trans Jakarta. This study identifies key success factors, such as thorough planning, strong government support, and efficient management, as well as major challenges, including lack of system integration, infrastructure issues, and limited public awareness. In conclusion, although both systems share similar objectives, the success of mass transportation system implementation largely depends on contextual factors, including geographical and demographic conditions, as well as the level of political support.